Chlorination of Soluble Residual Organics in Sewage Effluents - Zaloum, Ronald (My University, 1972)
Filtered final effluent was chlorinated at various doses using calcium and sodium hypochlorite in order to study the effect of chlorination on the soluble organics present in final effluents. The biochemical oxygen demand (BOD) was measured over a period of five days and carbon analyses (TOC) were performed during the course of the reaction. Chemical oxygen demand tests (COD) on filtered chlorinated-dechlorinated and unchlorinated sewage at various doses were also performed. It was found that chlorination did not bring about a BOD5 reduction nor rendered the soluble organics bioresistant or toxic to micro-organisms, owing to the presence of ammonia, as there was no significant difference in the extent of carbon degradation. The COD as well as TOC before and after chlorination remained unchanged indicating that there was no loss of organic content due to chlorination.
The pure compounds, glutamic acid, alanine, histidine, glycine, ammonia, phenol, n-butylamine, acetic acid and maleic acid were chlorinated at various chlorine doses in the presence and absence of ammonia and with chloramines. Glutamic acid and phenol were chlorinated at various pH levels. The oxidation of glycine by sodium hypochlorite was also studied. It was found that pH influences the rate of reaction considerably and that the presence of ammonia, whether free or combined as chloramines, slowed down the rate and prevented the oxidation of glycine from occurring.
The effect of chlorine residuals on the seed micro-organisms was also investigated. Three levels of residuals, 0.2, 0.5 and 0.8 mg/1 available chlorine, were employed. The chlorine demand of the sewage was satisfied prior to the addition of these residuals. The BOD was also monitored over a period of five days. The results indicated that longer lag phases resulted from the application of higher residuals and the lowest BOD was observed to occur at the highest residual. However, some microorganisms survived chlorination as evidenced by the exertion of a BOD at the 0.8 mg/1 available chlorine level.
The seeding technique employed by previous workers for measuring the BOD5 of unfiltered chlorinated-dechlorinated sewage was also investigated. It was found that even when the unchlorinated sample was not seeded, it contained a higher microbial concentration as evidenced by plate counts performed on both chlorinated-dechlorinated seeded and unchlorinated unseeded samples at two dilutions commonly employed in BOD5 determinations. Associated with these results was a BOD4 reduction of about 2.2 mg/1/mg/1 Cl absorbed. Seeding of the samples, at best, provides a uniformly mixed microbial population but not necessarily a uniform microbial concentration. These results could possibly explain the BOD5 reductions observed on unfiltered chlorinated effluents.
Keywords: chlorination, soluble, residual, organics, sewage effluents